Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is required for induction of autophagy during lumen formation in vitro - Mills, Kenna R. (National Academy of Sciences, 2004)
The molecular events regulating the elimination of cells to create a hollow lumen during tissue development are poorly understood. By using an in vitro morphogenesis model in which MCF-10A human mammary epithelial cells form hollow acini-like structures, we have observed both caspase-mediated apoptosis and autophagy associated with cells that are lost during lumen formation. Here, we show that the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) mediates induction of autophagic processes associated with lumen formation. TRAIL is up-regulated during morphogenesis of MCF-10A mammary epithelial cells in 3D basement-membrane cultures and inhibition of TRAIL signaling during morphogenesis blocks the formation of autophagic vacuoles. In addition, treatment with exogenous TRAIL induces extensive autophagy in monolayer and 3D cultures. When combined with inhibition of caspase 3 activity (by Bcl-X(L) overexpression), inhibition of TRAIL-induced autophagy results in luminal filling. Thus, TRAIL regulates an autophagic program during acinar morphogenesis, which together with caspase-mediated apoptotic events, results in lumen formation during MCF-10A morphogenesis.